The Correlation Between Occupational Factors and the Severity Level of Carpal Tunnel Syndrome (CTS) Among Dentists - Kumala, Andhini; Zadry, Hilma Raimona; Jumeno, Desto (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2026)
Carpal Tunnel Syndrome (CTS) is common condition that causes pain and functional disturbances in the hands and wrist, resulting from injury to the median nerve. This study aims to analyze the relationship between occupational factors and the severity of Carpal Tunnel Syndrome (CTS) among dentists, along with potential preventive strategies. In Indonesia, data on CTS prevalence remain limited. The research method utilized the Boston Carpal Tunnel Questionnaire (BCTQ) to assessed the severity of CTS among dentists and the statistical tests are used to test the correlation between occupational factors with the severity of CTS. Correlation analysis revealed that occupational factors such as daily working hours, excessive force application, age, years of professional experience, and regular medication usage significantly affect CTS severity and symptoms like tingling. The findings revealed that these factors significantly influence the severity of CTS. These results provide a foundation for developing more effective preventive strategies to improve the occupational health of dentists.